Phenolic Azobenzene as Ligand for Cation Complexation—Syntheses and Applications - Jan Hočevar; Jernej Iskra; Estelle Leonard (Molecules, 2025)
Phenolic azobenzenes have garnered significant attention as functional materials due to their ability to undergo reversible photoisomerization and their potential for cation complexation. This review aims to provide a comprehensive overview of the recent developments in the synthesis, properties, and applications of phenolic azobenzene derivatives in cation binding and complexation. This article explores various synthetic strategies for the preparation of phenolic azobenzenes. Additionally, the mechanisms of cation complexation, including the role of the phenolic hydroxyl group and the azobenzene scaffold, are discussed, along with insights into the coordination chemistry involved. This review further examines the diverse applications of phenolic azobenzene complexes in fields such as ion sensing, catalysis, and biological and DSSC applications.